2014
DOI: 10.3109/09638288.2014.948141
|View full text |Cite
|
Sign up to set email alerts
|

Visual disability rates in a ten-year cohort of patients with anterior visual pathway meningiomas

Abstract: Anterior visual pathway meningiomas (AVPMs) are commonly not life-threatening but they can lead to profound visual disability, especially when the tumor originates in the tuberculum sellae and cavernous sinus. Particular attention should be paid to visual acuity and visual field deficits, as these can profoundly affect the patient's quality of life including ability to drive and activities of daily living. The interdisciplinary management of patients with AVPM should include the neurosurgeon, neuro-ophthalmolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The wide use of magnetic MRI has aided in identifying correctly the site of origin in most meningiomas, but even today, ACMs are still often reported with suprasellar meningiomas. Our patient rapidly sought health services upon recognizing the early symptoms of visual loss, which is typical in cases of type III ACM [2,3,9]. To date, there is no guideline for the management of parasellar meningioma, especially ACM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wide use of magnetic MRI has aided in identifying correctly the site of origin in most meningiomas, but even today, ACMs are still often reported with suprasellar meningiomas. Our patient rapidly sought health services upon recognizing the early symptoms of visual loss, which is typical in cases of type III ACM [2,3,9]. To date, there is no guideline for the management of parasellar meningioma, especially ACM.…”
Section: Discussionmentioning
confidence: 99%
“…There are some therapeutic options including the microsurgical transcranial approach, endoscopic endonasal approach and radiosurgery or yet the combination of these modalities. However, now there is no consensus on the best technique [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, less attention has been paid to the effect that visual disability has upon patient’s career and employment [ 61 ]. Bor-Shavit et al [ 8 ] examined the postoperative visual outcome in skull base meningiomas close to the optical pathway and found that, regardless of the cause or origin of the disability, a visual impairment in patients who are unilaterally blind or unable to drive has a major impact on the patient’s VRQOL. Unilateral impairment of VRQOL is strongly associated with impaired distant, near, and stereo vision, and equally has important vocational and occupational implications.…”
Section: Methodsmentioning
confidence: 99%